An Analysis of Eutrophication Pattern in Phewa Lake Using Remote Sensing Technique - Bhattarai, Nischal; Pokhrel, Rajib (Himalayan Journal of Applied Science and Engineering, 2026)
Eutrophication has emerged as a critical environmental issue for freshwater ecosystems, particularly in regions experiencing rapid urbanization and tourism growth. Phewa Lake, situated in Pokhara, Nepal, faces increasing ecological stress from untreated sewage discharge, stormwater runoff, and seasonal tourist influx. This study investigates the spatial and temporal patterns of eutrophication in Phewa Lake using Sentinel-2 satellite imagery from 2017 to 2024. Two spectral indices were employed; Normalized Difference Chlorophyll Index (NDCI) to evaluate chlorophyll-a concentration and Normalized Difference Water Index (NDWI) to evaluate turbidity and surface water conditions. Twenty-four cloud-free images representing pre-monsoon, monsoon, and post-monsoon periods were analyzed in ArcGIS and correlated with rainfall and tourism data to identify major eutrophication drivers. The results indicate elevated NDCI values during pre-monsoon and post-monsoon seasons, corresponding with higher anthropogenic activity and reduced water levels, while increased NDWI values during the monsoon season reflect dilution effects and improved water clarity. These findings demonstrate that eutrophication in Phewa Lake is primarily governed by human-induced factors and natural hydrological variations. The integration of remote sensing and GIS techniques offers a reliable, non-invasive, and cost-effective approach for long-term lake monitoring. This study underscores the need for sustainable wastewater management, stricter regulation of tourism-related pollution, and incorporation of satellite-based monitoring into freshwater management and policy frameworks for Phewa Lake and similar ecosystems.